A regulação social do trabalho em sistemas ERP - Ponce, Ana Maria Carlos (Universidade Federal de São Carlos, 2012)
The ERP - Enterprise Resource Planning is considered one of the most important strategies for organizations in a business scenario that reconfigures itself permanently. Most researches on this subject follows a pragmatic-interventionist orientation, predominantly, with an approach oriented to identify practices that could improve the results of ERP implementations for a series of organizational actors and few attentions has been directed to aspects of the regulation of work in the ERP environment. In this perspective, this work aims to verify how the regulation of activity by agents that interact directly with the ERP system occurs. The study was developed with the presupposition of the Theory of Organizational Act of Maggi, on three core issues: the transformation of task, coordination and cooperation. Other issues relevant to the study were addressed as the Ergonomics of the Activity. We performed a qualitative, descriptive research. For the stated purpose it was defined as a technical procedure of research the study of multiple cases. The choice of the companies fell upon those companies that adopted ERP system in the area of Planning and Production Scheduling, in different sectors of activities and that expressed a willingness to participate. With respect to data collection it were used multiple techniques: documentary, interviews and observation. The results showed that the ERP system does not include the variability of the production system and that the agents regulate the activity through the use of other tools.
Keywords: Sistemas de informação gerencial; ERP; Ergonomia; Regulação do trabalho; Modo operatório; Análise de atividade; Agir organizacional; ERP; Organizational action; Social regulation of work; ENGENHARIAS::ENGENHARIA DE PRODUCAO